MOTIVATION AS A FACTOR OF THE EDUCATIONAL PROCESS - Корнієнко, Людмила (SWorldJournal, 2025)
In the article the author analyzes the role of motivation in the educational process, examines the system of motives, paying attention to five main groups of motives. According to the author, social, communicative, cognitive motives and motives of respon